miR-125b controls monocyte adaptation to inflammation through mitochondrial metabolism and dynamics - Duroux-Richard, Isabelle (Blood, 2016)
Metabolic changes drive monocyte differentiation and fate. Although abnormal mitochondria metabolism and innate immune responses participate in the pathogenesis of many inflammatory disorders, molecular events regulating mitochondrial activity to control life and death in monocytes remain poorly understood. We show here that, in human monocytes, microRNA-125b (miR-125b) attenuates the mitochondrial respiration through the silencing of the BH3-only proapoptotic protein BIK and promotes the elongation of the mitochondrial network through the targeting of the mitochondrial fission process 1 protein MTP18, leading to apoptosis. Proinflammatory activation of monocyte-derived macrophages is associated with a concomitant increase in miR-125b expression and decrease in BIK and MTP18 expression, which lead to reduced oxidative phosphorylation and enhanced mitochondrial fusion. In a chronic inflammatory systemic disorder, CD14(+) blood monocytes display reduced miR-125b expression as compared with healthy controls, inversely correlated with BIK and MTP18 messenger RNA expression. Our findings not only identify BIK and MTP18 as novel targets for miR-125b that control mitochondrial metabolism and dynamics, respectively, but also reveal a novel function for miR-125b in regulating metabolic adaptation of monocytes to inflammation. Together, these data unravel new molecular mechanisms for a proapoptotic role of miR-125b in monocytes and identify potential targets for interfering with excessive inflammatory activation of monocytes in inflammatory disorders.